INVESTMENTS IN COMPANIES WITH NEGATIVE EQUITY: THE RETURN IS WORTH THE RISK? - Cescon, José Antonio; Decourt, Roberto Frota; Costa, Luciana de Andrade (Revista Gestão Organizacional, 2021)
This study analyzed the return and risk of an investment portfolio, composed only of shares of companies listed in B3 that presented Negative Equity (NE), in the period from 1998 to 2019. Considering the Efficient Market Hypothesis (FAMA, 1970), the rationality of investors, the stock market on the stock exchange, in relation to companies with PLN, theoretically should not be active or provide abnormal positive returns to investors, since, technically, companies would be insolvent. The method used was to build a portfolio for assets that had at least one year of trading on the stock exchange and had NE in this period. The number of shares (assets) was fluctuating, starting with 2 and ending with 44 shares. The results of the Portfolio were compared to a risk-free investment (Interbank Deposit Certificate – CDI) and a similar risk investment (Brasil 50 Index - IBrX50), this as a control portfolio. The results found indicate that it is possible to obtain abnormal positive results, but do not meet the risk and return ratio when compared to a risk-free investment. However, when compared to other risky investments, investing in companies with NE may make sense, since a portfolio with no judgment criteria presents a more attractive risk and return ratio than stock indexes. This study contributes to the literature, as it brings to the academic world the universe of companies with NE, notably concerning the returns that these companies can provide to investors and, also for being an unprecedented study in this approach in Brazil.